2011
DOI: 10.1002/bjs.7576
|View full text |Cite
|
Sign up to set email alerts
|

Operative notes do not reflect reality in laparoscopic cholecystectomy

Abstract: Operative notes do not adequately represent the actual LCs performed as they describe fewer important procedural steps. It is suggested that operative notes should include video recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…However, postoperatively, it cannot be clearly reproduced what exactly occurred during the surgical procedure. Currently, the only source of technical information about the surgical procedure is the operative note, which has been shown to be subjective and lacking in critical information 16. Systematic video registration of the procedure might be a solution, adding objective information to the traditional operative note.…”
mentioning
confidence: 99%
“…However, postoperatively, it cannot be clearly reproduced what exactly occurred during the surgical procedure. Currently, the only source of technical information about the surgical procedure is the operative note, which has been shown to be subjective and lacking in critical information 16. Systematic video registration of the procedure might be a solution, adding objective information to the traditional operative note.…”
mentioning
confidence: 99%
“…It has also been found that the accuracy of reported intraoperative notes on LC contains only onequarter of the steps actually including in LC, which indicates that aforementioned shortcutting is made also in reporting e.g. (Wauben et al 2011). These issues could be considered as problems relating to standardization.…”
Section: Discussion and Suggestions For Failure Prevention In Otmentioning
confidence: 99%
“…Unfortunately, operative notes alone often omit critical components of an operation when compared to video recording 4 ; routine surgical recording would add objectivity and assist quality improvement efforts. Laparoscopic footage can be easily retrieved from operating room recorders while open procedures may be captured using wearable technologies.…”
Section: Routine Video Documentation Use and Integrationmentioning
confidence: 99%
“…4 Rather than transmit patient photographs and video over nonencrypted cellular and email systems, as has become commonplace, this integration would reduce patient privacy loss. A concomitant benefit might be the Hawthorne effect: an improvement in quality due to awareness of video recording.…”
Section: Routine Video Documentation Use and Integrationmentioning
confidence: 99%